Cytotoxic and Mechanical Properties of Resins 3D Printed with Low-Cost Hardware for C2C12 Biohybrid Actuators - Ashlee S. Liao; Kevin Dai; Alaeddin Burak Irez; Anika Sun; Michael J. Bennington; Saul Schaffer; Bhavya Chopra; Ji Min Seok; Rebekah Adams; Yongjie Jessica Zhang; Victoria A. Webster-Wood (Scientific Data)
Abstract For biohybrid actuators, the properties of synthetic materials interfacing with living cells are crucial due to cellular chemical and mechanical sensitivities. 3D-printable resins exhibit a wide range of properties, but mechanical properties are frequently reported before sterilization. Additionally, biocompatibility must be assessed for specific use cases, including in the context of the cell type and printing procedures. Therefore, this data descriptor details a new dataset of cytotoxicity and material properties of six commercially-available resins (three rigid and three elastomeric) printed on a Phrozen Sonic Mini 8K and sterilized using 70% ethanol exposure or autoclaving. Experiments were designed to model C2C12-biohybrid conditions. Cytotoxicity analyses were conducted by directly culturing C2C12 with sterilized samples. For material characterization, uniaxial tension and compression tests with post-hoc Hookean and Yeoh models and print fidelity assessments were conducted for nonsterile and sterile samples. The mechanical properties were assessed after submersion in phosphate-buffered saline to mimic conditions in biohybrid applications. Overall, this dataset provided comprehensive testing on cytotoxicity and material properties for 3D-printable resins in C2C12-biohybrid applications.